Origin of post-maximum bump in luminous Type Ic supernova 2019stc. Issue 1 (22nd December 2021) - Chugai, Nikolai N; Utrobin, Victor P
ABSTRACT: We address the issue of the post-maximum bump observed in the light curve of some superluminous supernovae. We rule out the popular mechanism of a circumstellar interaction suggested for the bump explanation. Instead, we propose that the post-maximum bump is caused by the magnetar dipole field enhancement several months after the explosion. The modelling of SN 2019stc light curve based on the thin shell approximation implies that at the age of ∼90 d, the initial dipole magnetic field should be amplified by a factor of 2.8 to account for the post-maximum bump. The specific mechanism for the field amplification of the newborn magnetar on the time-scale of several months has yet to be identified.